Relationship of Socio-economic Profile of Gujjars (Pastoralists) with Knowledge and Adoption of Improved Animal Husbandry Practices - R. Jeelani , S. A. Khandi , M. Y. Beig , P. Kumar; M. S. Bhadwal (Indian Journal of Extension Education, 2014)
Gujjars are one of the major pastoral communities of India. The study was conducted in Jammu district of Jammu and Kashmir, with a view to find out the relationship of knowledge level and adoption of Gujjars regarding improved animal husbandry practices. The data was collected from 120 Gujjar respondents belonging to R.S Pura and Bishnah block of Jammu district with the help of structured interview schedule containing selected dependent and independent variable, through personal interview technique.The independent variables except age, occupation, herd size and land holding were positively associated with the dependent variables i.e. knowledge and adoption. Age and occupation were negatively and significantly related to the knowledge level and adoption. Herd size was negatively and insignificantly related to knowledge level, but significantly associated with adoption. Knowledge level of respondents was negatively and significantly related with land holding however it was insignificantly associated with adoption. Education, social participation, mass media exposure, risk orientation and exposure to training were significantly and positively associated with both the knowledge level and adoption of respondents. On the other hand, extension contact and economic motivation were positively and significantly associated with the knowledge level but insignificantly related to the adoption.